Gesturing beyond the Frame: Transnational Trauma and US War Fiction - Ruth A. H. Lahti (Journal of Transnational American Studies, 2012)
The convergent boundary between the fields of trauma theory and US war fiction has resulted in a narrow focus on the subjectivity of the American soldier in war fiction, which partly conditions American war fiction's privileging of the soldier-author. However, this focus on American soldiers does not adequately account for the essentially interactive nature of war trauma, and it elides the experiences of nurses and noncombatants on all sides of the battle while also obscuring women's distinctive war experiences, even when the fiction itself sometimes includes these dimensions. In this essay, Lahti argues that a transnational method can counter these imbalances in trauma theory and in studies of US war fiction. She engages Tim O'Brien's highly influential The Things They Carried from a transnational perspective by interrogating the text's figuring of the survivor author and focusing on critically neglected scenes of interaction between the American soldiers and Vietnamese civilians. In order to discern the way these scenes reveal the text's own struggle with its national US frame, she elaborates a methodology of close reading characters' bodily gestures to foreground the way that fiction offers a glimpse into war as a relational event, always involving two or more participants. In the case of The Things They Carried, this approach brings into view a heretofore unnoticed pattern of mimicry between the American characters and Vietnamese characters that reshapes our scholarly understanding of the text's representation of war trauma.